Advanced Academic Degree for Nurses: Challenges and Career Opportunities - Agga, Abdulkarim; Akmadul, Alfaida (Alta Dharma Publisher, 2023)
Background: Obtaining an advanced degree in a nursing career is a multifaceted career move that could open multiple opportunities that can hasten one's career. But despite the promise of endless possibilities that an advanced degree could offer, there are multiple challenges that a nurse must undergo to achieve one's degree. Objective: The study aimed to explore the lived experiences of working nurses simultaneously pursuing their advanced academic degrees. Methods: This study employed a qualitative-phenomenological design. The career nurse participants were chosen from the officially enrolled Master of Nursing (MN) or Master of Arts in Nursing (MAN) students at Western Mindanao State University's College of Nursing Graduate Program for the Academic Year 2019-2020. A total of 10 respondents were selected as data saturation was already present with such a number. The interview was the data gathering methodology, and thematic analysis was its method for data interpretation. Results: There were 2 two (2) themes identified; (1) Challenges Met and (2) Perceived Opportunities with multiple subthemes for each general theme. It was found that the following were the identified challenges of the respondents during the interview, and there were corresponding perceived opportunities available once challenges were addressed and the advanced degree was obtained. Conclusion: This study was able to identify the different challenges experienced by the nurses who are taking up their master's degree and the challenges they are experiencing it. Based on the identified themes, some challenges were essential for them to surpass to achieve the possible opportunities. Recommendation: Future research may be conducted to explore further and expound the different experiences of the nurses taking up the challenge of having an advanced degree. As this study shall influence future undertakings, the data shall prove its use as a benchmark to improve further the quality of advanced degrees available for career nurses